Kesiapan Pemerintah DKI Jakarta Dalam Agenda Setting Rancangan Peraturan Pengendalian Lalu Lintas Secara Elektronik - Apreda Nor Rochmah (Jurnal Niara, 2024)
The Electronic Road Pricing (ERP) policy or paid road policy is here as the newest innovation from the Regional Government of DKI Jakarta to solving the problem of Jakarta's traffic jams which are getting out of control every day. After going through a long journey, this ERP policy is contained in the legal basis for the Draft Regional Regulation (Raperda) for Electronic Traffic Control (PL2SE). The Raperda, which has entered the early stages of review by the DPRD, will be reviewed for its readiness in the study of the literature on this research as well as the agenda setting of the policy. The results obtained include the Regional Government of DKI Jakarta which has prepared regulations and a legal basis, determining road sections, and the time of implementation. However, the government still has many things to consider, including the tariffs that will be imposed on this ERP, the technology that will be used, the condition and quality of public transportation services and facilities to the management of the ERP policy that will be carried out. The agenda setting for this policy has a problem flow (policy stream) in Jakarta congestion which is already very difficult to control, where the contributing factors are the community's preference for private vehicles, the road capacity factor, the human (community) awareness factor for traffic order, and also the factor of unfinished infrastructure development.